Pengaruh Gaya Kepemimpinan Kepala Sekolah Dan Profesionalisme Guru Terhadap Kinerja Guru Di SMP Negeri 1 Gondang Nganjuk - Siti Arifatun Nasrifah; Makhromi (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2019)
This study, taking the theme of the influence of the principal's leadership style and professionalism of teachers on teacher performance in SMP Negeri 1 Gondang, Nganjuk. Principal's leadership style and teacher professionalism are important indicators of achieving effective and efficient performance in an educational institution. This research approach is quantitative with ex post facto design. The population was all 60 Gondang 1 Junior High School teachers, then 42 samples were selected by using the Disproportionate Stratified random sampling technique. Data collection instrument in the form of a questionnaire with a Likert scale which has 4 alternative answers. The research instrument was tested on 42 teachers. The instrument validity test used was content validity with experimental judgment techniques, while for instrument reliability the Alpha Cronbach formula was used. Data analysis uses simple regression and multiple regression.The result is that the principal's leadership at SMPN 1 Gondang is included in the good category with an average score of 55,1429, professionalism of teachers in the professional category with an average score of 54.5714, the teacher's performance falls into the very good category with an average of 45.0714. With a simple regression analysis, it is known: there is no significant influence of the principal's leadership style on the performance of teachers of SMPN 1 Gondang because only -, 093, teacher professionalism does not affect the teacher's performance because it is only -, 102, but there is a positive and significant influence on the principal's leadership style on teacher professionalism that is equal to 98.3%. The results of multiple regression analysis showed that there was a significant joint effect between the principal's leadership style and teacher professionalism on teacher performance at SMPN 1 Gondang, which was only 1.2%.